Thymus Gland Pathology Clinical, Diagnostic and Therapeutic Features - Lavini, Corrado; Moran, Cesar A.; Morandi, Uliano; Schoenhuber, Rudolf (Springer Milan : Imprint: Springer, 2008)
The thymus has been a mysterious gland for centuries. The awareness of its role has been progressing, in particular during the second half of the twentieth century. The thymic pathology is related to several complex congenital, non-oncological, and oncological diseases. Many of these illnesses require a multidisciplinary approach thus involving several specialists: the surgeon, the neurologist, the anesthetist, and the pathologist. For example, myasthenia gravis-the most challenging disease deriving from a thymic trouble-requires an accurate and multimodal treatment. The oncologic pathology of the thymus is likewise complex, and involves also the oncologist and the radiotherapist. In cases of congenital thymic diseases, a transplantation of the thymus can be taken into consideration. This volume is an update on the pathology of this gland and includes 24 chapters written by international and well-known experts. The whole thymic pathology is described and new concepts about the nosological classification and the thymic neoplasm staging system are reported. Some chapters are focused on the radiologic, mini-invasive, and surgical diagnosis, and other chapters deal with surgical and non-surgical treatments. Special chapters are devoted to myasthenia gravis and thymus transplantation. The book will appeal to all the specialists involved in the treatment of thymic pathology, but can also be of interest to practitioners, and undergraduate and graduate students. .